The fungus Clonostachys epichloë alters the influence of the Epichloë endophyte on seed germination and the biomass of Puccinellia distans grass - Górzyńska, Karolina; Olejniczak, Paweł; Węgrzyn, Ewa (Frontiers in Microbiology, 2023)
The fungal grass endophyte Epichloë typhina (Pers.) Tul. & C. Tul. (Ascomycota: Clavicipitaceae) grows intercellulary in aerial plant parts and reproduces asexually by invading host seeds. In this phase, it enhances seed production and germination, which accelerates its vertical spread. This relationship may be distorted by other seed-born fungi, whose spread is not so directly dependent on the success of the grass. Recently, the fungus Clonostachys epichloë Schroers has been observed on Puccinellia distans (L.) Parl. seeds originating from grass clumps infested with stromata, sexual structures of Epichloë typhina that are formed in spring on some host culms, preventing flower and seed development (‘choke disease’). C. epichloë shows mycoparasitic activity toward Epichloë stromata by reducing the production of ascospores, which are responsible for horizontal transmission of the fungus. The aim of this study was to investigate the effect of seed-borne C. epichloë on seed germination, as well as the size and weight of P. distans seedlings and to examine whether C. epichloë alters the influence of Epichloë in the early developmental stages of P. distans. The results showed that if C. epichloë acts on seeds together with E. typhina endophytes, the seeds were negatively affected due to the elimination of the positive effect of the latter in terms of both seed germination rate and seedling length. At the same time, C. epichloë increased the proportion of E. typhina-untreated germinated seeds. Additionally, only the joint action of the two fungi, E. typhina and C. epichloë, effectively stimulated seedling dry mass; the presence of E. typhina alone was not sufficient to noticeably affect seedling size. Based on the increasing commonality of C. epichloë on Epichloë stromata, as well as its potential to be used in biocontrol of ‘choke disease’, we should take a closer look at this fungus, not only in terms of its mycoparasitic ability, but also in terms of its cumulative impact on the whole Epichloë-grass system.